Simple methods to test the accuracy of MRgFUS robotic systems - Antoniou, Anastasia; Drakos, Theocharis; Giannakou, Marinos; Evripidou, Nikolas; Georgiou, Leonidas; Christodoulou, Theodora; Panayiotou, Natalie; Ioannides, Cleanthis; Zamboglou, Nikolaos; Damianou, Christakis A. (My University, 2021)
Background: Roboticassisted diagnostic and therapeutic modalities require ahighly accurate performance to be certiﬁed for clinical application. In this paper,three simple methods for assessing the accuracy of motion of magnetic resonanceguided focused ultrasound (MRgFUS) robotic systems are presented.Methods: The accuracy of motion of a 4 degrees of freedom robotic systemintended for preclinical use of MRgFUS was evaluated by calliperbased and mag-netic resonance imaging (MRI) methods, as well as visually by performing multipleablations on a plastic ﬁlm.Results: The benchtop results conﬁrmed a highly accurate motion in all axes ofoperation. The spatial positioning errors estimated by MRI evaluation were deﬁnedby the size of the imaging pixels. Lesions arrangement in discrete and overlappingpatterns conﬁrmed satisfactory alignment of motion trajectories.Conclusions: We believe the methods presented here should serve as a standard forevaluating the accuracy of motion of MRgFUS robotic systems.
Keywords: MRgFUS robotic devices; Motion accuracy; Simple evaluation methods